Some molecular studies related to leaf rolling in Ctenanthe Setosa - Terzi, Rabiye; Sağlam, Aykut (İstanbul Kültür Üniversitesi, 2008)
The changes in total RNA content under drought stress condition that eventually causes leaf rolling was investigated in Ctenanthe setosa, a member of Marantaceae family in Zingiberales. Degree of leaf rolling (%) and total RNA content were measured under drought stress condition. It was determined that total RNA content decreased while degree of leaf rolling was increasing. In addition, partial sequence of small subunit ribosomal DNA (18S rDNA) of Ctenanthe setosa was determined to use as a control marker in polymerase chain reactions (PCR) during molecular studies. When compared with presumably functional sequences, 18S rDNA partial sequence of Ctenanthe setosa shows greater complete sequence similarity of 18S small subunits of Marantochloa atropurpurea, Maranta bicolor and Calathea loeseneri which are the members of same family. Obtained sequence also resembled Strelitzia nicolai and Phenakospermum guyannense belonging another family, Strelitziaceae from Zingiberales order. In addition, it seemed like to Ravenala madagascariensis, Musa acuminate, Heliconia indica, Orchidantha fimbriata and Orchidantha siamensis from same order. These results have been pointed out that obtained 18S rDNA partial sequence is true for Ctenanthe setosa.
Keywords: Ctenanthe setosa; leaf rolling; 18S rDNA; partial sequence; Total RNA; yaprak haddeleme; kısmi bir sekans; Toplam RNA